Policy challenges for agroforestry implementation in Europe - Mosquera-Losada, María Rosa; Santos, Mário Gabriel Santiago; Gonçalves, Berta; Ferreiro-Domínguez, Nuria; Castro, Marina; Rigueiro-Rodríguez, Antonio; González-Hernández, María Pilar; Fernández-Lorenzo, Juan Luis; Romero-Franco, Rosa; Aldrey-Vázquez, Jose Antonio; Sobrino, Cristina Cabaleiro; García-Berrios, Julian Jesús; et al. (Frontiers in Forests and Global Change, 2023)
Agroforestry (AF) is a sustainable land use practice and system that increases the ecosystem services delivery from agricultural lands compared with treeless systems. Agroforestry can be considered a practice when linked to plot scale (silvoarable, silvopasture, homegarden, woody linear landscape strips and forest farming), and a system when associated with the global farm scale.The enhancement of the ecosystem services is associated with the use and promotion of the biodiversity caused by the presence of the trees that optimizes the use of the resources if adequate species are mixed. Agroforestry can be implemented at temporal and spatial scale. At temporal scale the use of woody perennials to increase soil fertility is a traditional technique that improves soil health and reduces the needs of using herbicides (for example the legume Ulex sown for a 10 years period in between crop cultiviation). Five agroforestry practices can be implemented at plot level: silvopasture, silvoarable/alley cropping, homegardens/kitchengardens, woody linear landscape strips and forest farming. A farm including these practices is considered an agroforestry system working at landscape level, when several farms are mixed. In spite of the acknowledge that AF has at European level for being included as part of the Pillar I and II, the spread of AF is limited across Europe. Four challenges, linked with the technical, economical, educational and policy development have been identified by the AFINET thematic network that, if addressed, may foster the policy adoption across the EU. This paper proposes 15 different policy recommendations to overcome them and the need of developing an AF strategy for the EU.